Discussões sobre o pensamento algébrico que emergem em um curso de formação continuada para professores que ensinam matemática. - Santos, Marianna Cassa de Souza (2022)
This paper discusses the education of Math teachers of the early years of elementary school and their professional practices through the development of a continuing education course, proposing discussions about the development of algebraic thinking in the